Effect of experimental warming on soil respiration under conventional tillage and no-tillage farmland in the North China Plain - Chun TU; Fa-dong LI; Yun-feng QIAO; Nong ZHU; Cong-ke GU; Xin ZHAO (Journal of Integrative Agriculture, 2017)
Understanding the response of soil respiration to global warming in agro-ecosystem is crucial for simulating terrestrial carbon (C) cycle. We conducted an infrared warming experiment under conventional tillage (CT) and no-tillage (NT) farmland for winter wheat and summer maize rotation system in North China Plain (NCP). Treatments include CT with and without warming (CTW and CTN), NT with and without warming (NTW and NTN). The results indicated that warming had no significant effect on soil moisture in irrigated farmland of NCP (P>0.05). The elevated average soil temperature of 1.1–1.6°C in crop growing periods could increase annual soil CO2 emission by 10.3% in CT filed (P>0.05), but significantly increase it by 12.7% in NT field (P<0.05), respectively. The disturbances such as plowing, irrigation and precipitation resulted in the obvious soil CO2 emission peaks, which contributed 36.6–40.8% of annual soil cumulative CO2 emission. Warming would enhance these soil CO2 emission peaks; it might be associated with the warming-induced increase of autotrophic respiration and heterotrophic respiration. Compared with un-warming treatments, dissolved organic carbon (DOC) and soil microbial biomass carbon (MBC) in warming treatments were significantly increased by 11.6–23.4 and 12.9–23.6%, respectively, indicating that the positive responses of DOC and MBC to warming in both of two tillage systems. Our study highlights that climate warming may have positive effects on soil C release in NCP in association with response of labile C substrate to warming.